Breath Biomarkers of Influenza Infection. (21st September 2022) - Danaher, Patrick J; Phillips, Michael; Schmitt, Peter; Richard, Stephanie A; Millar, Eugene V; White, Brian K; Okulicz, Jason F; Coles, Christian L; Burgess, Timothy H
Abstract: Background: Volatile organic compounds (VOCs) are produced systemically due to varied physiological states such as oxidative stress and are excreted through the lungs. Benchtop and preliminary clinical data suggest that breath testing may be a useful diagnostic modality for viral respiratory tract infections. Methods: Patients with influenza-like illness (ILI) presenting to a single clinic in San Antonio, Texas, from 3/2017 to 3/2019 submitted a 2-minute breath sample in addition to a nasopharyngeal swab collected for polymerase chain reaction (PCR) assay for respiratory pathogens. VOCs were assayed with gas chromatography–mass spectrometry (GC-MS), and data were analyzed to identify breath VOC biomarkers that discriminated between ILI patients with and without a polymerase chain reaction (PCR) assay that was positive for influenza. Results: Demographic, clinical, PCR, and breath data were available for 237 episodes of ILI, among which 32 episodes (13.5%) were PCR positive for influenza. Twenty candidate VOCs identified patients with influenza with greater than random accuracy. A predictive algorithm using 4 candidate biomarkers identified this group with 78% accuracy (74% sensitivity, 70% specificity). Based on their mass spectra, most of these biomarkers were n-alkane derivatives, consistent with products of oxidative stress. Conclusions: A breath test for VOC biomarkers accurately identified ILI patients with PCR-proven influenza. These findings bolster those of others that a rapid, accurate, universal point-of-care influenza diagnostic test based on assay of exhaled-breath VOCs may be feasible. The next step will be a study of patients with ILI using a simplified method of breath collection that would facilitate translation for use in clinical practice. Abstract : A breath test utilizing volatile organic compound (VOC) biomarkers accurately identified patients with PCR-proven influenza. These findings bolster those of others that a rapid, accurate, universal point-of-care influenza diagnostic test based on assay of exhaled breath VOCs may be feasible.